NFM-08. SAFETY AND EFFICACY OF TRAMETINIB IN THE MANAGEMENT OF CHILDREN WITH RASOPATHIES. Issue 2 (22nd June 2018) - Bavle, Abhishek; Choudhry, Farooq; Gavula, Theresa; Shah, Rikin; Ruiz-Elizalde, Alejandro; Taylor, Ashley; Gross, Naina; Peterson, Jo Elle; Fung, Kar-Ming; McNall-Knapp, Rene
Abstract: BACKGROUND: There is emerging evidence regarding the efficacy of agents targeting the MAPK pathway in children with RASopathies. We report our experience with the use of trametinib, a MEK inhibitor, in this population. METHODS: Three patients with neurofibromatosis type 1 (NF-1) and plexiform neurofibromas refractory to imatinib, and 4 patients with low grade gliomas (LGGs) (3 NF-1; 1 encephalocraniocutaneous lipomatosis), with progression on multiple chemotherapy regimens (carboplatin/vincristine; vinblastine; bevacizumab/irinotecan) were treated with trametinib (median dose 1 mg/m2/day; 0.7 - 1.5 mg/m2/day) Tumor response was evaluated by MRI using RECIST (Response Evaluation Criteria in Solid Tumors) criteria. RESULTS: All patients with plexiform neurofibromas had stable disease (median follow-up 8 months), but reported improvement of vision, cosmesis and snoring respectively. Of 3 patients with optic pathway glioma, one had partial response, two had stable disease, and 1 of these patients had complete response of a cerebellar LGG (median follow-up 8 months). Two patients were taken off-therapy due to grade III adverse events, with bleeding scalp excoriations within 2 weeks, and pyogenic granulomas of multiple fingers and toes 5 months after treatment initiation, respectively. One patient needed 25% dose-reduction for grade II mouth sores. Six patients developed grade 1-2 maculopapular rash on the face, trunk or arms, with improvement using steroid and emollient ointments. CONCLUSION: MEK inhibitors can be effective in the treatment of multiply-progressive cranial and peripheral nerve tumors, in patients with RASopathies. Long-term follow-up in a larger study population is needed to determine the efficacy and adverse effects of these agents.